2014
DOI: 10.12927/hcpol.2014.23728
|View full text |Cite
|
Sign up to set email alerts
|

Provincial Disparities of Growth Hormone Coverage for Young Adult Survivors of Paediatric Brain Tumours across Canada

Abstract: Background: Young adult survivors of paediatric brain tumours (PBTs) who have been treated with radiation therapy will likely be severely growth hormone-deficient when retested at the achievement of final height. Growth hormone replacement therapy (GHRT) is administered to treat growth hormone deficiency (GHD). Public drug coverage for GHRT falls under the responsibility of provincial governments across Canada. This study sought to determine the extent of public drug coverage and cost in each Canadian province… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Our finding of heterogeneity in Canada's public drug programs is consistent with prior work; however, the differences across jurisdictions found in other reviews were attributed to the lack of programs for certain subpopulations, 8 drug costs not exceeding the required premiums or deductibles to receive assistance, 7 or differences in formulary listing. 9 In contrast, while we found that all jurisdictions listed most antiretrovirals and, with the exception of Newfoundland and Labrador, each had a program to provide coverage for all subpopulations, the main differences in coverage were due to variations in the amount of individual subsidies based on criteria. In 6 jurisdictions, antiretrovirals were fully covered with an HIV diagnosis being the only requirement for eligibility aside from having provincial/territorial health coverage; in the remaining regions, income Research and age primarily determined the subsidy received.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our finding of heterogeneity in Canada's public drug programs is consistent with prior work; however, the differences across jurisdictions found in other reviews were attributed to the lack of programs for certain subpopulations, 8 drug costs not exceeding the required premiums or deductibles to receive assistance, 7 or differences in formulary listing. 9 In contrast, while we found that all jurisdictions listed most antiretrovirals and, with the exception of Newfoundland and Labrador, each had a program to provide coverage for all subpopulations, the main differences in coverage were due to variations in the amount of individual subsidies based on criteria. In 6 jurisdictions, antiretrovirals were fully covered with an HIV diagnosis being the only requirement for eligibility aside from having provincial/territorial health coverage; in the remaining regions, income Research and age primarily determined the subsidy received.…”
Section: Discussionmentioning
confidence: 57%
“…Consequently, Canadians with identical prescriptions may pay substantially different amounts and may rely on private insurance, public funders, out-of-pocket payments or a combination of these to pay for their medication. [7][8][9] Financial burdens are associated with medication nonadherence. 10 Research indicates that medicine costs sometimes compete with other demands, leading to cost-related nonadherence: patients may forego prescribed medications in favour of spending their resources on other priorities or they may alter a medication's dosing to make a prescription last longer.…”
mentioning
confidence: 99%